Shape Optimization of a Column Modelling the Bridge Span under a Specific Load - Numerical and Experimental Studies - Janusz Szmidla; Anna Jurczyńska (Communications, 2023)
This work is dedicated to the problem of optimizing the shape of columns modelling bridge span subjected to the selected specific load case. Based on Hamilton's principle, motion equations and boundary conditions were defined. Taking into account the static criterion of loss of stability and the condition of constant volume of systems, the values of geometric parameters of the analyzed column were determined at which the maximum critical load value was obtained. The simulated annealing algorithm was used to find the maximum critical force being a function of many variables. Within the kinetic criterion of loss of stability, the range of changes in the natural frequency of optimized columns as a function of external load was determined. Based on the obtained results it was concluded that it is possible to control the dynamic properties while improving the stability of the system.